Forbedringsseminar som metode for å styrke sykepleiestudenters kompetanse innen forbedringsarbeid og fremme pasientsikkerhet innen legemiddelhåndtering - Reime, Marit Hegg; Østervold, Monica Jørstad; Haugsmyr, Eli; Remme, Åsa Rommetveit; Lybak, Kari; Jørgensen, Øyvind; Kvam, Fred Ivan (Nordisk Tidsskrift for Helseforskning, 2013)
AbstractQuality improvement seminar as a method to improve nursing students’ competence in the field of quality improvement and as a method to promote patient safety in medication managementQuality improvement projects between academia and clinical practice are in demand. The aim of this project was to develop and test an improvement method which could be implemented in a busy clinical hospital environment. An action research inspired approach was used. The action consisted of a quality improvement seminar where nursing students, teachers and nurses from clinical wards analyzed six case reports related to adverse events in medication management. Questionnaires determining the competence of nursing students related to improvement in medication management were used in a pretest - posttest study. Findings showed a significant improvement both in knowledge about the quality improvement process (p = 0.001) and about adverse events of medication (p = 0.005). On a scale from 0 (not suited) to 7 (particularly well suited), students scored 6.0 related to learning outcome of the quality improvement seminar. Quality improvement seminars seem to be effective for stimulating reflection on adverse events related to medication management.